Horst Opaschowski: Pedagogy of life with free time and the (de)politicization of leisure (Research, Society and Development, 2022)
One of the biggest problems of contemporary globalized society is the need to make private and personal time positive with a focus on mental and physical health, resignifying beyond the theory, the terms free time, leisure, leisure and recreation. In view of this context, this article seeks to fill existing gaps in the studies of German leisure time pedagogy, at the same time raising the debate on this topic in the context of education in Brazil. This essay consists of a systematic review of historical-descriptive literature, based on works by Horst Opaschowski and complemented by contemporary theorists such as: Gerhard Schulze, Reinhold Popp, Wolfgang Nahrstedt, Heinz-Hermann Krüger and Winfried Marotzki, Theo Dietrich and Michael Weegen. In the end, the danger of depoliticizing life with free time in today's society is discussed.